Overview of Platelet Levels of Patients with Pulmonary Tuberculosis at Kabila Health Center - Tiara Elpiana Djafar; Yolan Dunggio; Rita Amini Warastuti (LPPM Universitas Bina Mandiri Gorontalo, 2022)
The purpose of this study was to determine the results of the examination of normal and abnormal levels of platelets in patients with pulmonary tuberculosis and the causative factors that influence these levels. This research method used a descriptive quantitative approach method. The population in this study were all patients with pulmonary tuberculosis at the Kabila Health Center as many as 23 patients. The sample used was 23 respondents using the Total Sampling technique. The results showed that the abnormal platelet levels were 14.6% and normal platelet levels were 82.6%. Patients aged 15-50 years have abnormal platelet levels (17.4%) and normal platelet levels (82.6%). Patients with an age range of >50 years had normal platelet levels (21.7%). Male patients had normal platelet levels (26.1%), while women had abnormal platelet levels (17.4%) and had normal platelet levels (56.5%). Patients weighing 30-35kg 8.7% had abnormal platelet levels, and 4.34% had normal platelet levels. At 36-45 kg of body weight, 8.7% had abnormal platelet levels and 65.2% had normal platelet levels. At 46-55 kg of body weight, 8.7% had normal platelet levels and at 56-65 kg, 4.3% had normal platelet levels. Another factor is the length of treatment. In patients with two months of treatment, 8.7% had normal platelet levels, 17.3% had abnormal platelet levels, and 74% had normal platelet levels